รูปแบบการอธิบายเรื่องภพภูมิเพื่อแก้ปัญหาเรื่องกรรม และการเกิดใหม่ในสังคมปัจจุบัน - (สุพรรณ เตจ๊ะ), พระครูโสภิตพัฒนโชติ; ปันธิยะ, พูนชัย; จันทร์แรง, เทพประวิณ; ราชวัตร, สยาม (วารสารพุทธศาสตร์ศึกษา, 2024)
This research had three main objectives: 1) to study the concept of phap phum (realms of existence) as found in the Pali Canon, 2) to explore the relationship between phap phum and other Buddhist teachings, and 3) to propose a model for explaining phap phum that addresses issues related to karma and rebirth in contemporary society. The research findings indicate that phap phum in Buddhism has multiple meanings, including the state of existence within various realms, the condition of possessing or experiencing certain phenomena, and the concept of karma and the cycle of birth and death (samsara) as described in the Pali Canon. Phap phum is categorized into three levels: 1) kama bhava (realm of sensual desire), 2) rupa bhava (realm of form), and 3) arupa bhava (realm of formlessness). The analysis of the relationship between phap phum and other Buddhist teachings revealed two key aspects: 1) a cosmological or ontological structure that explains the arising and dissolution of realms according to the law of anicca (impermanence), and 2) a psychological process that emphasizes the internal formation of phap phum through ignorance, craving, and clinging. These two perspectives are intricately connected to Buddhist ethics, integrating metaphysical concepts with moral philosophy. In proposing a model for explaining phap phum to address issues of karma and rebirth in modern society, the research suggests applying the doctrine of dependent origination (paticca-samuppada) with a focus on present-life experiences that can be empirically verified. This approach emphasizes the value of present happiness and suffering over those in the afterlife, without rejecting the metaphysical aspects of phap phum and the cycle of rebirth. It highlights the benefits that can be realized in this life, suggesting that once individual and societal problems are properly addressed, concerns about the afterlife become secondary. This approach remains consistent with the Buddhist belief in samsara. Keywords: Realms of existence, Karma, Rebirth